Trace elements in soils and plants - Kabata-Pendias, Alina (Boca Raton, Florida : CRC Press, 2010)
"This fourth edition of a bestseller reflects the explosion of research during the past decade regarding trace elements and the environment related to the soil-plant system. It provides information on the biogeochemistry of trace elements in the soil-plant system and how these elements control our food quality. It discusses the assessment of natural/background content of trance elements in soil, bioindication of chemical status of environmental compartments, soil remediation, and hyperaccumulation and phytoextraction of trace metals from the soil. The table of contents reflects the IUPAC's recommendation for numbering element groups, giving the new edition an updated organizational flow"--
ch. 1. The biosphere -- ch. 2. The anthroposphere -- ch. 3. Soils and soil processes -- ch. 4. Soil constituents -- ch. 5. Trace elements in plants -- ch. 6. Elements of group 1 (Previously group Ia) -- ch. 7. Elements of group 2 (Previously group IIa) -- ch. 8. Elements of group 3 (Previously group IIIb) -- ch. 9. Elements of group 4 (Previously group IVb) -- ch. 10. Elements of group 5 (Previously group Vb) -- ch. 11. Elements of group 6 (Previously group VIb) -- ch. 12. Elements of group 7 (Previously group VIIb) -- ch. 13. Elements of group 8 (Previously part of group VIII) -- ch. 14. Elements of group 9 (Previously part of group VIII) -- ch. 15. Elements of group 10 (Previously part of group VIII) -- ch. 16. Elements of group 11 (Previously group Ib) -- ch. 17. Trace elements of group 12 (Previously of group IIb) -- ch. 18. Elements of group 13 (Previously group IIIa) -- ch. 19. Elements of group 14 (Previously group IVa) -- ch. 20. Elements of group 15 (Previously group Va) -- ch. 21. Elements of group 16 (Previously group VIa) -- ch. 22. Elements of group 17 (Previously group VIIa).
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Soils -- Trace element content; Plants -- Effect of trace elements on; Plants -- Composition; Trace elements; Plant-soil relationships; Electronic books